1996
DOI: 10.1046/j.1423-0410.1996.7120090.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Progenitor Cell Yield in a Leukapheresis Product by Previous Measurement of CD34+ Cells in the Peripheral Blood

Abstract: To assess whether measurement of CD34+ cells in the peripheral blood allows one to estimate the progenitor cell yields of subsequent leukapheresis procedures, 733 corresponding blood and leukapheresis samples were analyzed. Peripheral blood progenitor cells of cancer patients were mobilized with hematopoietic growth factors alone or postchemotherapy, and harvested processing 10 liters of blood for each leukapheresis product. The CD34+ cell count (CD34+ cells/microliter blood) correlated most closely with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…Our results demonstrate a very strong correlation between the number of CD34+ progenitor cells circulating in the peripheral blood and their yield in leukapheresis products, and are in accordance with recently published data; however, the minimum threshold of CD34+ cells in the peripheral circulation prior to initiating apheresis is still controversial [8, 9, 10, 11, 12, 13]]. Schots et al [8]showed that 10 CD34+ cells/µl peripheral blood can result in a harvest of at least 0.5×10 6 CD34+ cells/kg BW, whereas Chapple et al [12]demonstrated a threshold of 5 CD34+ cells/µl to obtain a minimum of 0.5×10 6 CD34+ cells/kg BW.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results demonstrate a very strong correlation between the number of CD34+ progenitor cells circulating in the peripheral blood and their yield in leukapheresis products, and are in accordance with recently published data; however, the minimum threshold of CD34+ cells in the peripheral circulation prior to initiating apheresis is still controversial [8, 9, 10, 11, 12, 13]]. Schots et al [8]showed that 10 CD34+ cells/µl peripheral blood can result in a harvest of at least 0.5×10 6 CD34+ cells/kg BW, whereas Chapple et al [12]demonstrated a threshold of 5 CD34+ cells/µl to obtain a minimum of 0.5×10 6 CD34+ cells/kg BW.…”
Section: Discussionsupporting
confidence: 91%
“…Taking all of this together, however, our finding reinforces the extreme importance of the flow cytometric monitoring of CD34+ cells for clinical decision making. The MNC count showed only a weak correlation (r = 0.374) with the collected CD34+ cells/kg BW, whereas the WBC count failed to predict the harvest of progenitor cells (r = 0.005), confirming previously published data [9, 10, 12]. Thus, the determination of WBC number is not suitable to replace the monitoring of CD34+ cells, which is still to be recommended for collecting stem cells efficiently and optimizing the use of financial and economic resources.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Centres advocating its use recommend commencing apheresis when the total WCC rises to between 3-10 · 10 6 /l (Watts et al, 1997). Most groups, however, demonstrate poor correlation between WCC and harvest CD34 (Möhle et al, 1996;Schots et al, 1996;Yu et al, 1999) and do not recommend basing a decision to commence apheresis on this value alone. In our group of patients the total WCC did not predict the timing of a successful apheresis.…”
Section: Discussionmentioning
confidence: 99%
“…Mohle et al . [48] found a strong linear correlation between the blood CD34+ cell count and the yield of CD34+ cells in the apheresis product. Moreover, they showed that 1 × 10 6 /kg CD34+ cells were collected in less than 5% harvests done with the blood CD34+ cells of < 10 µL.…”
Section: When To Harvest and How Much Is Required?mentioning
confidence: 99%